Mathematical morphology and poset geometry - Alain Bretto; Enzo Maria Li Marzi (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to characterize morphological convex geometries (resp., antimatroids). We define these two structures by using closure operators, and kernel operators. We show that these convex geometries are equivalent to poset geometries.